Pengaruh Strategi Pembelajaran SETS (Science, Environment, Technology, Society) Dipadu Blended Learning Terhadap Kualitas Proses dan Persepsi Mahasiswa - Yatni, Asmaria Nursuci (Hydrogen: Jurnal Kependidikan Kimia, 2018)
The aim to study were to determine 1) the quality of the learning process, and 2)students' perceptions of the learning. One of the strategies that couldaccommodate the learning is SETS approach combined with blended learning.The research used posttest only control design. The samples were IV semesterstudents who took chemistry environmental course which were consisted of classA (experimental group) class B (control group). The data were of quality of thelearning process obtained using observation sheets and student’s perceptionwhich is obtained with questionnaire.The results of the study were as follows.First, the quality of the learning process by using SETS learning strategiescombined with blended learning was better than by using SETS learningstrategies only. Second, students' perceptions of learning by using SETS learningstrategies combined with blended learning were more positive than using blendedlearning only.